Spatial distributions of sulphur species and sulphate-reducing bacteria provide insights into sulphur redox cycling and biodegradation hot-spots in a hydrocarbon-contaminated aquifer. (1st May 2015) - Einsiedl, Florian; Pilloni, Giovanni; Ruth-Anneser, Bettina; Lueders, Tillman; Griebler, Christian
Abstract: Dissimilatory sulphate reduction (DSR) has been proven to be one of the most relevant redox reactions in the biodegradation of contaminants in groundwater. However, the possible role of sulphur species of intermediate oxidation state, as well as the role of potential re-oxidative sulphur cycling in biodegradation particularly at the groundwater table are still poorly understood. Here we used a combination of stable isotope measurements of SO4 2−, H2 S, and S 0 as well as geochemical profiling of sulphur intermediates with special emphasis on SO3 2−, S2 O3 2−, and S 0 to unravel possible sulphur cycling in the biodegradation of aromatics in a hydrocarbon-contaminated porous aquifer. By linking these results to the quantification of total bacterial rRNA genes and respiratory genes of sulphate reducers, as well as pyrotag sequencing of bacterial communities over depth, light is shed on possible key-organisms involved. Our results substantiate the role of DSR in biodegradation of hydrocarbons (mainly toluene) in the highly active plume fringes above and beneath the plume core. In both zones the concentration of sulphur intermediates (S 0, SO3 2− and S2 O3 2− ) was almost twice that of other sampling-depths, indicating intense sulphur redox cycling. The dual isotopic fingerprint of oxygen and sulphur in dissolved sulphate suggested a re-oxidation of reduced sulphur compounds to sulphate especially at the upper fringe zone. An isotopic shift in δ 34 S of S 0 of nearly +4‰ compared to the δ 34 S values of H2 S from the same depth linked to a high abundance (∼10%) of sequence reads related to Sulphuricurvum spp. ( Epsilonproteobacteria ) in the same depth were indicative of intensive oxidation of S 0 to sulphate in this zone. At the lower plume fringe S 0 constituted the main inorganic sulphur species, possibly formed by abiotic re-oxidation of H2 S with Fe(III)oxides subsequent to sulphate reduction. These results provide first insights into intense sulphur redox cycling in a hydrocarbon contaminant plume, which widens the perspective of redox processes and microbial interactions ongoing in contaminated aquifers.